2016
DOI: 10.1055/s-0036-1572526
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Processing Assessment in Children with Attention Deficit Hyperactivity Disorder: An Open Study Examining Methylphenidate Effects

Abstract: Introduction Children with Attention Deficit Hyperactivity Disorder can present Auditory Processing (AP) Disorder. Objective The study examined the AP in ADHD children compared with non-ADHD children, and before and after 3 and 6 months of methylphenidate (MPH) treatment in ADHD children. Methods Drug-naive children diagnosed with ADHD combined subtype aging between 7 and 11 years, coming from public and private outpatient service or public and private school, and age-gender-matched non-ADHD children, particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…It is possible to observe similar characteristics in subjects with developmental disorders such as ASD and AD/HD. Previous studies have reported that children with AD/HD showed sensory processing deficits, and APD and AD/HD have overlapping clinical characteristics ( Ghanizadeh, 2009 , Lanzetta-Valdo et al., 2017 ). Moreover, some studies argued that compared with controls, ASD subjects showed poorer scores on some auditory processing tests ( DePape et al., 2012 , Mamashli et al., 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…It is possible to observe similar characteristics in subjects with developmental disorders such as ASD and AD/HD. Previous studies have reported that children with AD/HD showed sensory processing deficits, and APD and AD/HD have overlapping clinical characteristics ( Ghanizadeh, 2009 , Lanzetta-Valdo et al., 2017 ). Moreover, some studies argued that compared with controls, ASD subjects showed poorer scores on some auditory processing tests ( DePape et al., 2012 , Mamashli et al., 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, ADHD participants’ perception of both CLR and NV speech was shown to be differential to controls even in quiet. It is, however, not uncommon in the literature that individuals with ADHD show impairments on central auditory processing tasks even though they have normal peripheral hearing (e.g., Gascon et al, 1986; Lanzetta-Valdo et al, 2016; Fostick, 2017). Indeed, a subject of some controversy is whether central auditory processing disorder is a distinguishable diagnosis from ADHD (Moss and Sheiffele, 1994; Riccio and Hynd, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of central stimulant medication has also been shown to improve both auditory processing and the subjective experience of listening effort and background noise disturbance in persons with ADHD (Keith and Engineer, 1991; Freyaldenhoven et al, 2005; Lanzetta-Valdo et al, 2016). Although the use of stimulant medication in children is controversial and the long-term health risks are still being investigated (c.f.…”
Section: Discussionmentioning
confidence: 99%
“…Classroom behaviors observed include difficulty listening. Children with ADHD exhibit deficits in specific auditory skills such as auditory closure, binaural integration, and temporal ordering (Lanzetta‐Valdo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%